Familisme dalam Manajemen Rumah Makan Sederhana di Kota Makassar - Emanuel Omedetho Jermias; Mauliadi Ramli; Abdul Rahman (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2023)
The Micro, Small and Medium Enterprises sector, including simple restaurant business activities in Makassar City, contributes to the economy. This study aims to reveal the management of family-based restaurants and their implications for creating wealth, especially within the family environment. The method used in answering the research objectives, then carried out observations, interviews, and document studies. The results of the study show that restaurant owners prefer to recruit employees from family and relatives based on the moral economy approach. The selection of employees with a moral economy approach for restaurant owners is intended so that these employees can obtain a more prosperous level of economic life and a more proper education.